(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The histological diagnosis of neurogenic tumors remains a challenge, which may be indicated particularly by the fact that new entities appeared in the new edition of the World Health organization (WHO) classification. Purpose: To review the histomorphologic and immunohistochemic features of rare variants of neurogenic ocular (retinal) tumors in adults. Material and Methods: Six rare ocular tumors were selected for the study from all clinical material submitted for pathohistological examination from 2017 to 2020 based on the presence of morphological evidence of neurogenic differentiation. Results: The study sample of six rare neurogenic retinal tumors in adults was conventionally divided into three types: (1) retinal tumors immunohistochemically similar to cellular ependymoma, but histologically similar to retinoblastoma; (2) tumors showing no histological pattern characteristic for dictyoma, but the immunohistochemical features of neuroepithelial differentiation; and (3) tumors showing histological patterns similar to medulloepithelioma, but the immunohistochemical features of glial markers. Conclusion: Obviously, when dividing these tumors into histogenetic groups, not only the histological structure and immunohistochemical profile, but also tumor location and typical patient age should be taken into account.